2013
DOI: 10.21273/jashs.138.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Genetic Analysis of Three Important Nutritive Traits in the Fruit of Avocado

Abstract: Avocado (Persea americana) is a subtropical tree prized for its large and nutritious fruit. Although native to Mesoamerica, avocado is now grown in tropical and subtropical regions around the world, and consumer demand for avocado continues to grow at a considerable rate. Despite the appeal of avocado, its genetic improvement has been slow owing to substantial land and labor requirements combined with the fact that young trees do not produce fruit for several years and a poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…Alpha-tocopherol content exhibited moderate to high heritability in quantitative genetic analyses (Calder on-V azquez et al, 2013;Chen et al, 2007) and might be expected to yield some success in breeding programs. The current mapping studies suggest that the variation underlying flowering type and a-tocopherol may be the result of mutations at a single genetic locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha-tocopherol content exhibited moderate to high heritability in quantitative genetic analyses (Calder on-V azquez et al, 2013;Chen et al, 2007) and might be expected to yield some success in breeding programs. The current mapping studies suggest that the variation underlying flowering type and a-tocopherol may be the result of mutations at a single genetic locus.…”
Section: Discussionmentioning
confidence: 99%
“…Yet only the genetic component of a phenotype will respond to breeding. Two studies in avocado (Calder on-V azquez et al, 2013;Chen et al, 2007) used quantitative genetics to tease apart the genetic and the environmental components of the phenotypic value of a suite of quantitative traits. Chen et al (2007) demonstrated for the progeny of cultivar Gwen that major growth-related traits, such as plant height and trunk-and canopy diameter, were under genetic control and showed sufficient heritability to respond to selection.…”
mentioning
confidence: 99%
“…race (Bergh and Ellstrand, 1986). Previous research about the effect of the selected avocado rootstocks over crop performance has shown that trees of the same variety grafted to Mexican or Guatemalan race rootstocks differ in their susceptibility to Phytophtora cinnamomi (Smith et al, 2011;Reeksting et al, 2016;Sánchez-González et al, 2019), in their mineral nutrient uptake (Bard and Wolstenholme, 1997;Calderón-Vázquez et al, 2013), and in their response to salinity (Mickelbart and Arpaia, 2002;Raga et al, 2014). For instance, Bernstein et al (2001) demonstrated that even in selected rootstocks chosen by exhibiting excellent fruit production under elevated NaCl-condition, there is a wide range of growth sensitivities that results in growth inhibition or growth stimulation under salt-levels typically found at commercial fields.…”
Section: N R E V I E Wmentioning
confidence: 99%
“…cinnamomi (Smith et al, 2011;Reeksting et al, 2016;Sánchez-González et al, 2019), mineral nutrient uptake (Bard and Wolstenholme, 1997;Calderón-Vázquez et al, 2013), and response to salinity (Bernstein et al, 2001;Mickelbart and Arpaia, 2002;Raga et al, 2014). However, harvest/quality traits have not been explicitly considered in previous studies that aimed assessing rootstock effects on 'Hass' avocado.…”
Section: N R E V I E Wmentioning
confidence: 99%
“…Previous studies have developed molecular markers for avocado including SNPs from targeted resequencing (Chen et al 2008), and microsatellite markers (Alcaraz and Hormaza 2007;Ashworth et al 2004;Borrone et al 2007;Ge et al 2019;Gross-German and Viruel, 2013;Lavi et al 1994;Mhameed et al 1997;Sharon et al 1997). These markers have been combined with phenotypic data including heritability of nutritional components (Calderon-Vazquez et al 2013) and have been used to identify marker trait associations in avocado (Mhameed et al 1995;Sharon et al 1998). A recent study identified > 250,000 polymorphic SNPs from 22 avocado individuals (Ge et al 2019).…”
Section: Introductionmentioning
confidence: 99%